2007
DOI: 10.1108/08876040710737868
|View full text |Cite
|
Sign up to set email alerts
|

To do or not to do: the dilemma of technology‐based service improvement

Abstract: PurposeThe purpose of this paper is to suggest a conceptual framework to examine customer satisfaction with a technology‐based service improvement. Three factors are suggested that influence customers' acceptance of the improved service: internal, consistency and external (ICE).Design/methodology/approachHypotheses are constructed by reviewing literature in the areas of customer satisfaction, marketing services and diffusion of innovation. An exploratory study was conducted in an academic setting, to examine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Our study mirrors the results of previous scholars which are ease of use (Curran & Meuter, 2005;Timmor & Rymon, 2007) and usefulness (Lin et al, 2007;Walker & Johnson, 2006) that were found to be among the main factors of consumer intention to adopt SST. This shows that the constructs are empirically reliable and valid where it explains the various types of technology adoption in numerous economies (countries) and in different context (multiple industries).…”
Section: Discussionsupporting
confidence: 79%
“…Our study mirrors the results of previous scholars which are ease of use (Curran & Meuter, 2005;Timmor & Rymon, 2007) and usefulness (Lin et al, 2007;Walker & Johnson, 2006) that were found to be among the main factors of consumer intention to adopt SST. This shows that the constructs are empirically reliable and valid where it explains the various types of technology adoption in numerous economies (countries) and in different context (multiple industries).…”
Section: Discussionsupporting
confidence: 79%
“…The use of students as participants is common in adoption research (for example, Hill et al, 1987;Lee and Allaway, 2002;Lim and Dubinsky, 2004;Timmor and Rymon, 2007). Furthermore, Keen (1999) found no difference in predicting consumer decisions regarding Internet use between students and mall shopper samples.…”
Section: Participantsmentioning
confidence: 96%
“…Cronin et al, 2000), little attention has been given to customer satisfaction with service improvements (Timmor and Rymon, 2007). Since technology can enable increased levels of service through greater customization and flexibility , we expect customer satisfaction to be positively affected by service improvements reached, thanks to the technological solutions implemented by retailers.…”
Section: It In the Context Of Relational Marketingmentioning
confidence: 98%
“…To evaluate this aspect, it is essential to measure the effects of IT solutions on perceived quality and consumer satisfaction (Gurau and Ranchhod, 2002;Weinstein, 2002;Servera et al, 2006). Little attention, however, has been given to customer satisfaction with technology-based improvements and/or upgrading of existing services (Timmor and Rymon, 2007) and the differences across service activities (Drennan and McColl-Kennedy, 2003), even though both factors should be considered in investment decisions. In fact, several types of retailers analyzed in the literature present peculiarities (Berry and Barnes, 1987) that may make difficult the extrapolation some investment patterns to other retail activities.…”
Section: Introductionmentioning
confidence: 99%